Formation and growth of metallic iron microparticle during carbothermic reduction of red mud with palm kernel shell charcoal - Agung Setiawan; Adji Kawigraha; Boy Attaurrazaq; Sebastian Nahar; Nur Vita Permatasari; Irwan Haryanto; Nur Ikhwani; Sri Harjanto; M. Akbar Rhamdhani (Case Studies in Chemical and Environmental Engineering)
The present study investigated the formation and growth behavior of metallic iron microparticles during the carbothermic reduction of red mud using palm kernel shell charcoal (PKSC) as a reducing agent. The experiments involved both thermodynamic simulations and experimental reduction work. The thermodynamic calculations predicted that liquid and solid metal, slag, mullite, corundum, and spinel would form as the main phases through the reduction process at 600–1500 °C. The experimental result revealed that the identified phases were metallic iron, spinel, and corundum when the reduced pellets reacted up to 1400 °C for 60 min. The total weight loss of a mixture of red mud and PKSC was estimated at 22.12 % based on thermogravimetric analysis. The metallization degree of iron in the reduced pellets increased with increasing the reduction temperature and the reaction time. The maximum metallization degree and mean size of iron metallic microparticles were obtained at 97.2 ± 0.7 % and 36.79 μm, respectively, when the reduced pellet was heated at 1400 °C for 60 min. The microstructure observations showed that when the temperature and reaction time increased, the metallic iron microparticles formed, sintered together, and progressively grew.